“Put Me in, Coach”: A Discussion of Deprescribing Roles, Responsibilities, and Motivations Based on a Qualitative Study with Healthcare Professional Students - Devin Scott; Amy Hall; Rachel Barenie; Crystal Walker; Muneeza Khan; Paul Koltnow; William R. Callahan; Alina Cernasev (Pharmacy)
As the US population ages, the number of prescriptions managed by patients and healthcare teams is increasing. Thus, discontinuing or reducing medications that are considered to pose more risks than benefits can be achieved through deprescribing. Despite increasing calls for a stronger focus on deprescribing in healthcare education, current discussions highlight the lack of training on this topic within healthcare curricula. This is a significant barrier to effectively implementing the deprescribing process. This study aimed to characterize healthcare professional students (HPSs)’s perspectives on deprescribing within an interprofessional healthcare team, particularly regarding the motivations and roles of these future practitioners. Methods: Focus groups were conducted with HPSs at the University of Tennessee Health Science Center. The data collection, guided by a conceptual model, took place over three months in 2022. Data analysis was performed using thematic analysis, during which themes were identified through inductive coding. Results: Participants (n = 36) represented various faculties, including medicine, pharmacy, health professions, nursing, and dentistry. Two themes emerged: (1) Healthcare Team Members’ Roles and Responsibilities (2) “Put Me in, Coach”: Patient Safety Motivates Deprescribing. Conclusion: Data from HPSs highlighted the importance of an interprofessional healthcare team approach to deprescribing. Based on these insights, educators and practitioners should focus on establishing strong interprofessional healthcare teams that privilege open communication. Teams should consider deprescribing as a patient safety concern, as this may galvanize the team and provide additional motivation for performing the necessary work of deprescribing.